2016
DOI: 10.21273/hortsci.51.6.775
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Frequency Distributions for Fruit Firmness of Sweet Cherry Cultivars

Abstract: Fruit firmness is among the most important characteristics for the quality of sweet cherries. However, little has been published on its underlying frequency distribution. This research was undertaken to examine the firmness distributions (n = 48) from six cultivars [Sandra Rose, Summit, Lapins, Skeena, Sumtare (Sweetheart™), and 13S2009 (Staccato™)], two field treatments [with or without gibberellic acid (GA)], two storage times (0 and 7 days), and two growing seasons (2013 and 2014). Fruit was sampled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Seed number is typically positively associated with fruit weight and is significantly influenced by pollination efficiency (Gray and Coombe, 2009). Precisely determining fruit weight is essential in horticulture for estimating yield and the proportion of marketable fruits (Pathak et al, 2016;Stanich et al, 2016). However, despite its significance, there is a dearth of published research concerning the fundamental distribution of strawberry fruit weights.…”
Section: Introductionmentioning
confidence: 99%
“…Seed number is typically positively associated with fruit weight and is significantly influenced by pollination efficiency (Gray and Coombe, 2009). Precisely determining fruit weight is essential in horticulture for estimating yield and the proportion of marketable fruits (Pathak et al, 2016;Stanich et al, 2016). However, despite its significance, there is a dearth of published research concerning the fundamental distribution of strawberry fruit weights.…”
Section: Introductionmentioning
confidence: 99%
“…For manual fruit picking, there are recommended relatively natural crown shapes with a height of trees of 3-3.5 m, with a central shaft and cup-shaped. Indifferent the crown form, in trees grafted on reduced vigor rootstocks (Gisela 5, Gisela 6, Gisela 12 Krymsk 5 Krymsk 6) it is important to apply a suitable system in order to form vertical branches of the semi scheleton, which ensures high-quality fruits and easy manual picking (Asanica, 2012, Long, et al, 2014;Stanich et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The fruit firmness in sweet cherry cultivars was studied in Canada (Stanich et al 2016), where a principal component analysis showed the seasonal, culti-https://doi.org/10.17221/70/2021-HORTSCI var, treatment, and storage effects among three subsets of cultivars with differing characteristic firmness. The softer early-harvest cultivars had a higher proportion of "too soft" fruit.…”
mentioning
confidence: 99%